2008
DOI: 10.1063/1.2987685
|View full text |Cite
|
Sign up to set email alerts
|

Development of new in situ observation system for dynamic study of lubricant molecules on metal friction surfaces by two-dimensional fast-imaging Fourier-transform infrared-attenuated total reflection spectrometer

Abstract: To observe the time-dependent two-dimensional (2D) images of spatial distribution of chemically/physically modified lubricant molecules on the metal surface during friction motion, a new in situ technique has been developed by combining the 2D fast-imaging Fourier-transform infrared-attenuated total reflection spectrometer with the temperature-controlled friction equipment containing lubricant agent. Using this new instrument, the time-dependent changes in lubricant molecules, for example, cis-trans isomerizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Vibrational spectroscopies, not requiring ultra-high vacuum for carrying out analytical studies, provide valuable insights into the chemical reactions taking place within the rubbing interface [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Although the literature demonstrated the possibility of investigating the chemical composition [23][24][25] and the conformation of the lubricant film [15,26], the pressure distribution within the contact [27] as well as the third bodies formed by solid lubricants in the contact [4][5][6][7][8][9][10][11][12], the necessity of replacing one of surfaces with an IR-transparent window can have significant implications for the study of the tribochemistry of lubricant additives and solid lubricants.…”
Section: Comparison Of the Newly Developed In Situmentioning
confidence: 99%
See 1 more Smart Citation
“…Vibrational spectroscopies, not requiring ultra-high vacuum for carrying out analytical studies, provide valuable insights into the chemical reactions taking place within the rubbing interface [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Although the literature demonstrated the possibility of investigating the chemical composition [23][24][25] and the conformation of the lubricant film [15,26], the pressure distribution within the contact [27] as well as the third bodies formed by solid lubricants in the contact [4][5][6][7][8][9][10][11][12], the necessity of replacing one of surfaces with an IR-transparent window can have significant implications for the study of the tribochemistry of lubricant additives and solid lubricants.…”
Section: Comparison Of the Newly Developed In Situmentioning
confidence: 99%
“…Among the analytical techniques used for carrying out in situ tribological investigations, molecular spectroscopies (i.e., infrared and Raman spectroscopy) were found to provide a valuable insight into the chemical reactions taking place under steady-state conditions [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], but always require one of the rubbing surfaces to be transparent to the wavelength of radiation concerned.…”
Section: Introductionmentioning
confidence: 99%
“…Since these techniques require a high-vacuum environment, the specimens are measured ex situ after the oil has been completely removed, often by ultrasonic cleaning with an organic solvent such as hexane or acetone. However, many researchers have pointed out that washing with solvents may alter the tribofilm structures and exposure to the air may cause oxidation [1][2][3]5,6].…”
Section: Introductionmentioning
confidence: 99%
“…As in situ measurements under the lubrication condition require a condition in ambient, Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), and Raman spectroscopy are candidates for the measurements. In situ FT-IR tribometry has been widely adopted to investigate the changes in lubricants [1,5,7,8], while in situ XRD tribometry is suitable for investigating the changes in the crystalline structure near the surface. Kajita et al [9] recently investigated the scuffing of SUJ2 steel using synchrotron radiation XRD, and they observed that the martensite to austenite phase transformation occurred during scuffing in a dry friction condition.…”
Section: Introductionmentioning
confidence: 99%
“…Infrared (IR) absorption spectroscopy [2][3][4][5][6][7][8][9][10][11][12][13][14][15] and Raman spectroscopy [16][17][18] are particularly attractive tools for studying buried interfaces nondestructively. There are many practical and interpretational problems associated with the application of Raman and IR spectroscopy to in-contact studies.…”
Section: Introductionmentioning
confidence: 99%